Vulnerable and neglected: Middle class exclusion in Indonesia’s socio- economic policy dynamics - Damayanti, Salsabila; Solicha, Sughmita Maslacha Amala; Mas'udah, Siti; Sulaiman, Sabri (Faculty of Social and Political Science, Universitas Airlangga, 2025)
The middle class in Indonesia is increasingly recognized as one of the most vulnerable segments of society in relation to poverty. This study aims to critically examine public policy, focusing specifically on the socioeconomic aspects of the middle class, which systematically create new forms of vulnerability and exclusion. Utilizing a quantitative research design, the study employed a closed-ended questionnaire as its primary data collection instrument, involving a total of 846 respondents. Data analysis was conducted using univariate techniques with SPSS 25. The findings indicate that Indonesia’s middle class is entangled in multidimensional poverty and experiences widespread patterns of social exclusion. This includes not only economic vulnerability but also exclusions related to social structures, public policy, health, environment, technology, and digitalization, as well as cultural identity and other crisis-related domains. The study reveals that the social exclusion of the middle class within Indonesia’s socioeconomic policy frameworks produces structural vulnerabilities that may exacerbate social inequality, restrict economic mobility, and undermine long-term social stability. Although often portrayed as a symbol of national prosperity, the middle class is, in reality, caught in a cycle of vulnerability, marginalization, and neglect by prevailing policy approaches. Consequently, the study calls for developing more inclusive and responsive strategic frameworks and policy models capable of protecting the middle class from the emergence of a precariat condition, the phenomenon of middle class squeeze driven by downward mobility, and the broader transformation toward a dualistic society.